Vaccination status of children aged 1–4 years in Afghanistan and associated factors, 2015. Issue 34 (16th August 2018) - Shenton, Luke M.; Wagner, Abram L.; Carlson, Bradley F.; Mubarak, Mohammad Yousuf; Boulton, Matthew L.
Abstract: Background: Childhood mortality in Afghanistan fell by half between 1990 and 2015, due in part to the government's commitment to improving pediatric immunization services. Although progress has been made, immunization coverage has nonetheless remained low with only 65% of children receiving the third dose of Diphtheria-Pertussis-Tetanus (DPT3) based on WHO estimates. This study aims to calculate the proportion of Afghan children aged 1–4 years who were fully vaccinated, under-vaccinated, or non-vaccinated with government-recommended Expanded Program on Immunization vaccines and identify predictors related to the family's sociodemographic status and maternal autonomy. Methods: Data from the 2015 Afghanistan Demographic and Health Survey was used to calculate the proportion of children who were fully vaccinated (i.e. received all recommended vaccines), under-vaccinated (i.e. received some, but not all), and non-vaccinated (i.e. did not receive any vaccines) according to WHO guidelines. A multivariable multinomial logistic regression model generated odds ratios for under-vaccination and non-vaccination versus full vaccination, and examined associations between independent factors and full vaccination status. Results: We found 40.6% of Afghan children age 1–4 were fully vaccinated, 42.4% under-vaccinated, and 17% non-vaccinated. Large disparities characterized immunization coverage among provinces and between urban and rural regions. Birthing in a government institution (vs. non-institutional setting), a higher number of antenatal care visits, and a visit to a health facility in the past 12 months were all associated with increased odds of full immunization. Factors related to maternal autonomy including maternal decision-making and maternal attitudes towards beating were also significantly associated with vaccination status. Conclusion: Approximately 60% of children in Afghanistan are under-vaccinated or non-vaccinated, leaving millions of children unnecessarily at risk for vaccine-preventable diseases. Engagement with community and religious leaders to create programs that increase women's autonomy and expand access to institutional delivery could lead to downstream increases in childhood vaccination coverage.